2020
DOI: 10.20944/preprints202002.0136.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tick-borne Encephalitis Virus Vaccines Contain Non-structural Protein 1 (NS1) Antigen and May Elicit NS1-Specific Antibody Responses in Vaccinated Individuals

Abstract: Vaccination against tick-borne encephalitis (TBE) is based on the use of formalin-inactivated, culture-derived whole-virus vaccines. Immune response following vaccination is primarily directed to the viral envelope (E) protein, the major viral surface antigen. In Europe, two TBE vaccines are available in adult and pediatric formulations, FSME-IMMUN® (Pfizer) and Encepur® (GlaxoSmithKline). Herein, we analyzed the content of these vaccines using mass spectrometry (MS). The MS analysis revealed t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Several studies showed that NS1 immunization or passive transfer of anti-NS1 antibodies afforded protection against infections with flaviviruses, such as DENV, YFV and WNV in animal models [ 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. These findings have been confirmed for the TBEV NS1 protein [ 97 , 101 , 105 , 106 , 107 , 108 , 124 ]. Mouse studies showed that immunization with a synthetic peptide corresponding to the structurally conserved α-helix (aa37–55) of NS1 [ 108 ] or with various synthetic fragments of NS1 [ 101 ] induced partly protective immunity against lethal challenge infection with TBEV.…”
Section: Immune Response To Tbev Infection and Vaccinationmentioning
confidence: 62%
See 4 more Smart Citations
“…Several studies showed that NS1 immunization or passive transfer of anti-NS1 antibodies afforded protection against infections with flaviviruses, such as DENV, YFV and WNV in animal models [ 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. These findings have been confirmed for the TBEV NS1 protein [ 97 , 101 , 105 , 106 , 107 , 108 , 124 ]. Mouse studies showed that immunization with a synthetic peptide corresponding to the structurally conserved α-helix (aa37–55) of NS1 [ 108 ] or with various synthetic fragments of NS1 [ 101 ] induced partly protective immunity against lethal challenge infection with TBEV.…”
Section: Immune Response To Tbev Infection and Vaccinationmentioning
confidence: 62%
“…In its pentameric or hexameric form, NS1 is secreted into the extracellular space [ 11 ], inducing a NS1-specific antibody response. After natural TBEV infection, NS1-specific IgM and IgG antibodies are detectable at high levels in human sera ( Table 2 ) [ 94 , 95 , 96 , 97 ]. Several studies showed that NS1 immunization or passive transfer of anti-NS1 antibodies afforded protection against infections with flaviviruses, such as DENV, YFV and WNV in animal models [ 117 , 118 , 119 , 120 , 121 , 122 , 123 ].…”
Section: Immune Response To Tbev Infection and Vaccinationmentioning
confidence: 99%
See 3 more Smart Citations